Assessment in First Year University: A Model to Manage Transition - Taylor, J. (Journal of University Teaching and Learning Practice, 2008)
For most students assessment guides their study and learning practice. Yet in theliterature associated with the first year of study at university, few have mobilisedthe power of assessment to develop and engage first year undergraduate students.This paper presents a model of assessment for first year students which separatesthe semester into three overlapping assessment phases: assessment for transition,assessment for development and assessment for achievement. Theimplementation and usefulness of the model is supported by examples frommathematics, engineering, computing, communication and nursing studies at theUniversity of Southern Queensland (USQ). Particular attention is paid toassessments for transition which occur early in the semester and are linked moreclosely with processes than specific content. Evidence is collated on the success ofassessments in improving the participation of students, especially distanceeducation students.